Mental Health Among Sami Sexual Minority and Majority Youth in Norway - Knapp, Jonill Margrethe Fjellheim (UiT Norges arktiske universitet, 2022)
Previous international studies show that indigenous sexual minority youth experience more mental health problems than their sexual majority peers. Qualitative studies on Sami sexual minority people indicate high levels of stigma, as they are a minority within a minority. This study looks at differences in outcomes of mental health measurements between Sami sexual minority and sexual majority youth in Norway, and protective and risk factors of mental health. The Norwegian Arctic Adolescent Health Study was conducted among 10th graders in junior high schools in Northern Norway during 2003–2005. The study sample consisted of 450 Sami youth, of which 62 were sexual minority. Mental health outcomes were measured by Strengths and Difficulties Questionnaire (SDQ) internalizing and externalizing problems and prosocial behavior, in addition to self-reported health. Sociodemographic, environmental support, cultural and psychosocial factors were assessed. SPSS 28.0 was used to perform independent-samples T test, crosstabulation with chi-square tests, simple logistic regression and hierarchical multiple regression analyses. Statistical analyses showed significant differences in internalizing and externalizing problems, where Sami sexual minority youth scored higher than their sexual majority peers. No differences were found in prosocial behavior or self-reported health. Of risk factors that were significantly associated with more mental health problems, sexual minority youth reported more concerns about sexuality and negative life events, and less school wellbeing. Self-efficacy and peer support were identified as protective factors, and no differences were observed between Sami sexual minority and majority youth. In this study Sami sexual minority were found to report more internalizing and externalizing problems than Sami sexual majority youth. No difference was found for prosocial behavior and self-reported health. Some differences in risk factors were observed.